Water Quality Conditions and Effectiveness of Management of Lubuk Larangan in Bandur Picak Village, Kampar - Hanifa, Hanifa; Fauzi, Muhammad; Adriman, Adriman (Fakultas Perikanan dan Kelautan Universitas Riau, 2025)
Lubuk Larangan is a part of the river that has been used as a protected area for native fish resources in a particular area through traditional rituals. This research aims to analyze the water's physical and chemical parameters and assess the effectiveness of managing Lubuk Larangan in the Kampar River, Bandur Picak Village. This research was carried out from March to April 2024 in Lubuk Larangan, Bandur Picak Village. Data collection in this research used a survey method. The research location is divided into four observation station points: upstream non-Lubuk Larangan, Lubuk Pinang, Lubuk Batu Patah, and downstream non-Lubuk Larangan. The results of this research show that the water quality conditions, namely physical and chemical parameters, are still by river water quality standards with an average temperature of 24.97oC, brightness of 47.18 cm, current speed of 0.43 m, TDS 84.74 mg/L, depth of 2.36 m, pH 5, DO 7.33 mg/L, nitrate 0.05 mg/L, and phosphate 0.06 mg/L. The interview results on the effectiveness of the management of lubuk larangan conducted during the research were divided into three criteria: the criteria, management, and accommodation for lubuk larangan. The data shows that the management of lubuk larangan is included in the practical category.